Phenotypic diversity and plasticity index of Eurycoma apiculata populations in Eastern Sumatra, Indonesia based on leaves morphology - Zulfahmi Zulfahmi; Edi Purwanto; Parjanto; Ahmad Yunus (Society for Indonesian Biodiversity, 2020)
Abstract. Zulfahmi, Purwanto E, Parjanto, Yunus A. 2020. Phenotypic diversity and plasticity index of Eurycoma apiculata populations in Eastern Sumatra, Indonesia based on leaves morphology. Biodiversitas 21: 2923-2934. Eurycoma apiculata A.W. Benn. is a protected species in Indonesia, but diversity information of this species is limited. The objective of this study was to assess the phenotypic diversity, phenotypic plasticity index, and phenotypic differentiation among populations of E. apiculata in Eastern Sumatra, Indonesia based on leaves morphology. A total of 45 traits were measured on leaves from six populations studied. The result of this found that the phenotypic variation coefficient (CV) of the characters was ranged from 7.41% to 36.97%, revealed the abundant phenotypic variation in the species. The phenotypic CV values of the population varied from 13.95% to 24.10%. The CV values of all populations from the mainland Sumatra (17.75%) were lower than that from the Riau archipelago (23.61%), which revealed that phenotypic traits in mainland Sumatra were more stable compared to populations in the Riau archipelago. The population phenotypic plasticity index value of populations ranged from 0.41 to 0.51, and it was classified as a moderate level. The phenotypic differentiation coefficient among populations in this study was relatively low (VST = 21.06%), indicating a lower phenotypic variation among populations than within populations. The scatter plot of principal component analysis and UPGMA dendrogram divided the six populations studies into two groups. The findings of this study recommend that the in-situ conservation method is an effective protection strategy for E. apiculata while ex-situ conservation method can be implemented as a supplementary method.